1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1522::aid-immu1522>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The origin of marginal zone B cells in the rat

Abstract: The marginal zone is a unique compartment that is only found in the spleen. Rat marginal zone B cells (MZ-B) can be distinguished from other B cells, e.g. recirculating follicular B cells (RF-B), by several phenotypic characteristics. Typically MZ-B cells are surface (s)IgMhi, sIgDlo and CD45R(B220)lo, whereas RF-B cells are sIgMlo, sIgDhi and CD45Rhi. In addition, MZ-B cells stain strongly with HIS57, a newly developed monoclonal antibody. The developmental pathway and origin of MZ-B cells are not exactly kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 35 publications
1
52
0
1
Order By: Relevance
“…It was long held that MZB cells emanate from progenitors with a CD23 + T2B phenotype that express CD1d and CD21 6,10,17,41 . Others have also proposed that FoB cells can develop into MZB cells, particularly in immunodeficient and lymphopenic hosts, a process that might be driven by homeostatic proliferation 24,41,42 . Data from mice in which the repertoire of developing MZB cells was followed by measuring the junctional diversity of the heavy chain CDR3 region revealed that T1B cells were the most likely direct progenitors for MZB cells 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It was long held that MZB cells emanate from progenitors with a CD23 + T2B phenotype that express CD1d and CD21 6,10,17,41 . Others have also proposed that FoB cells can develop into MZB cells, particularly in immunodeficient and lymphopenic hosts, a process that might be driven by homeostatic proliferation 24,41,42 . Data from mice in which the repertoire of developing MZB cells was followed by measuring the junctional diversity of the heavy chain CDR3 region revealed that T1B cells were the most likely direct progenitors for MZB cells 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Because this niche is limited in the capacity to retain MZ B cells, an excess of V H T/ 2 B cells may reside in the follicle and acquire FO B cell phenotypes. Another possibility is that a part of FO B cells can be precursors of MZ B cells (16,17). By analyzing the molecular basis controlling the recruitment of V H T/ 2 B cells into these two microenvironments, the QM system will give a clue to gain insight into the development mechanism of MZ B cells.…”
Section: Discussionmentioning
confidence: 99%
“…2, 10, and 11). Although the origin of MZ B cells remains controversial, newly formed (NF) B cells are most likely the immediate precursors (12)(13)(14)(15), while an origin from FO B cells is also suggested (16,17). Accumulating evidence indicates that MZ B cells may be positively selected by BCR signals that might be distinct from those required for generating FO B cells.…”
Section: Analysis Of Marginalmentioning
confidence: 99%
“…The migration of Pten-deficient B cells, especially FOB cells, was greater than that of controls against SDF-1α as determined by the Transwell TM assay. Dammers et al have reported that MZB cells are derived from a subset of FOB cells by migration (Dammers et al, 1999). Knockout studies have shown that Pyk2 (Guinamard et al, 2000), Lsc (Girkontaite et al, 2001) and DOCK2 (Fukui et al, 2001), all molecules involved in cell motility, are indispensable for MZB formation.…”
Section: Role Of Pten In B Cellsmentioning
confidence: 99%